(untitled) (Journal of Hama University, 2022)
This study aims at recognizing the psychological burnout of teachers of persons with visual impairment at its relationship to some personality features The sample has consisted of (28) male/ female teachers of blind pupils at the Association of Blind in Hama city. The study used the descriptive analytic approach by applying Maslach Scale for psychological burnout and Izenk Scale personality features for the sample of teachers of persons with visual impairment. Data have been analysed using SPSS. The study shows that there is statistically significant relationship between psychological burnout and personality features for the teachers of persons with visual impairment in all dimensions. The results are as follows: - There is a strong positive statistical relation between (emotional stress, blunting affect, the feeling of lack of achievement) and personality features (neurosis) for the teachers of persons of visual impairment. - There is a strong negative statistical relation between (emotional stress, emotional blunting, the feeling of lack of achievement) and personality features (Extroversion, lying (social gravity) for the teachers of persons of visual impairment.